Analisis Pengaruh Penyekatan Kanal Untuk Untuk Pembahasan Lahan Gambut Tropis - Gina Khusnul Khotimah; Sigit Sutikno; Muhamad Yusa; Indradi Wijatmiko (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
Peatlands rewetting for hydrological restoration plays an important role in fire prevention and peatland restoration of degraded peatland. One of the methods for the rewetting is canal blocking. The impact of canal blocking for peatland rewetting is further analyzed in this research. This study focused in Pulau Tebing Tinggi peatland hydrological unit (PHU), which is located in Kepulauan Meranti Regency, Riau Province. To analysis the rewetting impact, 15 dipwells were installed with the distance of 1 m, 51 m, 101 m, 201 and 301 m from the canal for each transect of the three transects. A transect was set in the downstream and two transects were set in the upstream of canal block. The ground water level (GWL) in the 15 dipwells was recorded using water-loggers for one year. This research found that canal blocking has a good effect on maintaining groundwater levels and keeping peatlands in always wet or humid conditions up to a distance of 201 m perpendicular to the canal if the rise in water level in the canal due to canal blocking is more than 0.6 m. It is able to maintain the ground water depth in peatlands around 0.4 m, where the peatlands become low risk to the fire, emission rates and subsidence.